The validity of the Memory Alteration Test and the Test Your Memory test for community‐based identification of amnestic mild cognitive impairment. Issue 9 (2nd May 2016) - Ozer, Seline; Noonan, Krist; Burke, Melanie; Young, John; Barber, Sally; Forster, Anne; Jones, Roy
Abstract: Introduction: This study investigated the validity of two brief cognitive tests (Memory Alteration Test [M@T] and Test Your Memory [TYM] test) for identifying people with aMCI in the community. Methods: Older people were invited to participate by their general practitioner practice. Eligible participants were assessed for aMCI using an operationalized approach to the Petersen criteria and the M@T and TYM. Results: Both tests demonstrated significant ability in discriminating between people with aMCI and controls (AUC = 0.91 for M@T and 0.80 for TYM [ P  < .001 for both]). M@T performed with higher sensitivity than TYM (85% vs. 63%) and similar specificity (84% vs. 87%). Both tests demonstrated moderate test‐retest reliability (κ = ∼0.5) and took <10 minutes to administer. Discussion: M@T and TYM are quick to administer. M@T demonstrated higher diagnostic test accuracy than TYM and could provide an efficient method for identifying aMCI in clinical and research settings.